Belarus in Polish eastern policy during the Polish-Soviet War (1919-1920) - Miszewski, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The late 19th century saw a national awakening of the Belarusian people. During World War I, under German occupation, the Catholic Belarusian national movement intended to create a sovereign Belarusian state (the Belarusian People`s Republic) or in union with Lithuania (a revived Grand Duchy of Lithuania). After the February Revolution of 1917 in Russia, Orthodox national activists wanted a sovereign Belarus within a federal and democratic Russia. The Belarusian People`s Republic, established in March 1918, was not recognized by any state. Poland, Lithuania and Soviet Russia intended to incorporate the Belarusian lands on an autonomous basis. As a result of the Riga Peace Treaty (1921), the Belarusian lands were divided between Poland and Soviet Russia.
Keywords: Belarusian minority; Polish eastern policy; the Polish-Soviet war; Poland; Soviet Russia